2023
DOI: 10.3390/pathogens12020225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Biocontrol Efficiency of Bacillus subtilis Wettable Powder on Pepper Root Rot Caused by Fusarium solani

Abstract: The plant-growth-promoting rhizobacteria (PGPR) B. subtilis PTS-394 has been utilized as a biocontrol agent (in a wettable powder form) due to its excellent ability to suppress tomato soil-borne diseases caused by Fusarium oxysporum and Ralstonia solanacearum. In this study, we evaluated the biocontrol efficiency of Bacillus subtilis PTS-394 wettable powder on pepper root rot in pot experiments and field trials. B. subtilis PTS-394 and its lipopeptide crude extract possessed excellent inhibition activity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Currently, several strains of Bacillus spp. are used as biocontrol agents against crop diseases ( Bonaterra et al, 2022 ; Qiao et al, 2023 ; Idris et al, 2024 ). M. esculenta is an important edible fungus that has high economic, nutritional, and medicinal value.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several strains of Bacillus spp. are used as biocontrol agents against crop diseases ( Bonaterra et al, 2022 ; Qiao et al, 2023 ; Idris et al, 2024 ). M. esculenta is an important edible fungus that has high economic, nutritional, and medicinal value.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus species, in particular, have garnered significant research attention for advancing future biological control strategies (Shafi et al, 2017;Etesami et al, 2023;Poulaki and Tjamos, 2023). Currently, various antagonistic Bacillus species have been isolated and screened from soil, plants, and other environments, including B. amyloliquefaciens (Zheng et al, 2018;Wu et al, 2019;Jia et al, 2023;Markovićet al, 2023), B. velezensis (Reyes-Estebanez et al, 2020Chen et al, 2022;Yan et al, 2022), B. subtilis (Bais et al, 2004;Ding et al, 2017;Qiao et al, 2023), among others. Previous investigations highlight the inhibitory and anti-infection effects of B. amyloliquefaciens against pathogenic fungi causing diseases in rice, tomato, potato, brinjal and fruit (Jiao et al, 2020;Nie et al, 2022;Markovićet al, 2023;Pradhan et al, 2023;Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…tritici TSO2T as a promising biocontrol agent against Fusarium languescens , the causative agent of Fusarium wilt in chilies. Qiao et al (2023) reported significant biocontrol activity of Bacillus subtilis PTS-394 against Fusarium solani .…”
Section: Chili Disease Management Using Biocontrol Agentmentioning
confidence: 99%
“… Montoya-Martínez et al (2023) Bacillus subtilis PTS-394 Fusarium solani B. subtilis PTS-394 shown a good biocontrol activity against Fusarium solani at 63 % and 74.43 %. Qiao et al (2023) Bacillus cereus F-BC26 and Bacillus thuringiensis F-BT24 Xanthomonas euvesicatoria F-BT24 and F-BC26 strains formulations promoted Chilies growth and protected it against Xanthomonas euvesicatoria , a causative agent of bacterial spot disease. Hernández-Huerta et al (2023) Bacillus spp.…”
Section: Chili Disease Management Using Biocontrol Agentmentioning
confidence: 99%